2003
DOI: 10.1101/gad.1084703
|View full text |Cite
|
Sign up to set email alerts
|

Notch signaling regulates left–right asymmetry determination by inducingNodalexpression

Abstract: Generation of left-right asymmetry is an integral partGeneration of left-right asymmetry during development is an integral part of the establishment of the vertebrate body plan (Capdevila et al. 2000;Mercola and Levin 2001;Wright 2001;Yost 2001;Hamada et al. 2002). Specification of the left-right axis requires multiple steps: (1) generation of an initial asymmetric signal in or near the embryonic node, (2) transfer of asymmetric signals from the node to the lateral plate mesoderm (LPM), (3) induction of an evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
204
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(215 citation statements)
references
References 43 publications
(63 reference statements)
6
204
1
1
Order By: Relevance
“…A considerable number of studies have reported complete absence of nodal, lefty, or pitx2 expression (Field et al, 2011; Oki et al, 2010; Sakano et al, 2010; Gaio et al, 1999; Takeuchi et al, 2007; Zhang et al, 2001; Yan et al, 1999; Tsukui et al, 1999; Collignon et al, 1996; Kramer-Zucker et al, 2005; Krebs et al, 2003; Pennekamp et al, 2002), with some reporting 100% absent expression for all three genes. What does complete absence of gene expression mean?…”
Section: Discussionmentioning
confidence: 99%
“…A considerable number of studies have reported complete absence of nodal, lefty, or pitx2 expression (Field et al, 2011; Oki et al, 2010; Sakano et al, 2010; Gaio et al, 1999; Takeuchi et al, 2007; Zhang et al, 2001; Yan et al, 1999; Tsukui et al, 1999; Collignon et al, 1996; Kramer-Zucker et al, 2005; Krebs et al, 2003; Pennekamp et al, 2002), with some reporting 100% absent expression for all three genes. What does complete absence of gene expression mean?…”
Section: Discussionmentioning
confidence: 99%
“…The primary embryonic organizer, Spemann's organizer in the amphibian embryo, Hensen's node in rabbit and mouse, and the embryonic shield in the teleost fish embryo, from which the dorsal forerunner cells and hence Kupffer's vesicle (KV) are derived, thus sets the stage for the development of the PNC/GRP/KV or its equivalent in other vertebrates, which func-tionally may turn out to be primarily involved in LR axis development. Experimental manipulation of the organizer thus affects all three body axes, while defects in PNC/GRP/KV cause laterality defects without affecting the main body axes (Herrmann and Kispert, 1994;Nonaka et al, 1998;Krebs et al, 2003;Przemeck et al, 2003;Abdelkhalek et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In the post-implantation epiblast at E5.5, Nodal expression is controlled by pluripotency factors, and notably by OCT4 and by an auto-regulatory loop involving NODAL signalling (Adachi et al, 1999;Norris et al, 2002;Norris and Robertson, 1999). In addition, WNT3/β-catenin signalling triggers Nodal upregulation in the E6.5 posterior epiblast and primitive streak (Ben-Haim et al, 2006;Vincent et al, 2003), and NOTCH/RBPJ signalling controls its expression in the node from E7.5 (Krebs et al, 2003;Raya et al, 2003). The ectopic anterior expression of Nodal observed in E7.5 N1ICD epi embryos might result from a direct action of N1ICD/ RBPJ on the Nodal node-specific enhancer (NDE) (Adachi et al, 1999;Krebs et al, 2003;Norris and Robertson, 1999; Raya et al, 2003).…”
Section: Discussionmentioning
confidence: 99%